IDEOPATHIC JAUNDICE IN A MARE: A CASE REPORT - Bhorkatriya, DN; Gohil, KM; Kalasariy, RM; Mungad, KS; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The liver plays an important role in the equine digestive, endocrine, coagulation and immune systems. Its primary functions are detoxification, synthesis of proteins and biochemical products necessary for digestion.The liver is an organ with an extremely important reserve function and therefore it requires a loss of at least 60-80 % of organic mass to show signs of liver failure.The most common signs of liver disease in the horse are icterus (Fig. 1 & 2), behavioural change and weight loss. Other signs include photosensitisation, inspiratory stridor and occasionally diarrhoea